A POLITICO-IDEOLOGICAL ASPECT OF INTERCULTURALITY OF FRENCH LANGUAGE TEACHING IN THE POST-WAR SERBIA (1945-1953) - Биљана J. Стикић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
<!-- p { margin-bottom: 0.1in; line-height: 120%; } --> Interculturality, which is nowadays particularly in the focus of research in the area of language teaching methodology, has proved interesting in the diachronic perspective of the post-war French language teaching in Serbia, which was at that time a part of the Yugoslav Federation. With respect to the contents of the high-school curricula and of the two selected French course books published in Belgrade (1947, 1951), the politico-ideological aspect of interculturality was fully expressed, but in a particular manner. The first evident fact in the curricula, based on which the course books were edited, is a clear positioning of the politico-ideological principles of the post-war Yugoslav society with respect to the French society. The selected texts in the course books, written by French writers, served to explicitly or implicitly support the dominant ideological values of the Yugoslav Federation. This procedure was based on identifying commonalities in the events of the French Bourgeois Revolution, the Paris Commune and World War Two. A large number of topics of the lessons in the analyzed course books supported the values promoted during the observed period of the Yugoslav socialism, such as benefi ts of life in the country and the seasonal labor, the glorifi cation of labor and the working class as the bearer of progress, the optimism in the face of hardships of everyday life, the view of capitalism and aristocracy as state enemies, reactionary and regressive elements, and references to the fi ght against fascism and the need to help the weak and the feeble. Insistence on this kind of ideological approach, which, on the one side, ignored the facts about the everyday life of the French people, the French capitalist society and the period of the monarchy, and, on the other side, identifi ed the principles in the ideologically acceptable periods of French history that were equivalent to the principles of the Yugoslav socialist reality, refl ects a kind of interculturality which is to a certain extent deformed and which could also be described in this context as an ideological retrograde temporal transposition.